Facilitating gender transformation in small ruminant management through Community Conversations in Bide community, Konso, Ethiopia - Woldegiorgis, Mamusha; Dessalegn, Bezaiet; Dea, Dereje; Soka, Gehano (International Center for Agricultural Research in the Dry Areas, 2023)
Gender norms, attitudes and practices in rural areas hamper women’s empowerment and their ability to engage in issues that matter in their lives. Constraining gender relations at the household and community levels combined with limited gender capacities of service providers are hindering women’s participation in decision-making processes and limiting their access to and control over resources, assets and benefits including information, services, and technologies in livestock development. Addressing constraining gender norms and practices requires dialogues to change knowledge, attitudes, and practices (KAP) of community members and service providers. In recent years, community-based approaches have been receiving more attention because of their strong grassroots focus that enables service providers to develop informed interventions based on the local context. Community Conversations create inclusive spaces for dialogue, joint analysis, collaborative learning, and action, which facilitate changes in the KAP of community members and local service providers. Through dialogue and collaborative learning processes, the underlying gender values and norms that shape the behaviors and attitudes of community members and service providers as well as the patterns of interactions between women and men can be explored and addressed in livestock development.